New Development Model of the Agro-Industrial Complex Under Green Economy Conditions - Saparova, Dana; Saginova, Saniya; Belgibayeva, Kuralay; Bekbussinova, Gulnafiz; Kasenova, Asiya; Tleulin, Chingiz (Ital Publication, 2025)
This study empirically examines opportunities and provides a conceptual rationale for developing a green economy model tailored to Kazakhstan’s agro-industrial complex (AIC). The research focuses on identifying effective strategies for sustainable agricultural development by combining environmental and economic approaches. The methodological basis includes the analysis of theoretical concepts in economic and mathematical modeling, identification of key factors influencing the sector, and the construction of a block structure to represent these factors. Forecasting models were developed to evaluate the efficiency of various strategic directions for transitioning to sustainable agriculture. The findings indicate that the most influential drivers of sustainable development include the expansion of green financial instruments, increased public and international investment, and the use of digital technologies for collecting and processing data. The forecast of key indicators of the green economy in Kazakhstan up to 2030 confirms the reliability and applicability of the proposed evaluation method. The main contribution of this research is the creation of an integrated model that connects theoretical frameworks with practical tools for managing ecological and economic performance in agriculture. The results can be applied in strategic planning, decision-making for the AIC, and academic programs focused on the green economy and sustainable development in Kazakhstan.